Stikine Icefield Mass Loss between 2000 and 2013/2014 - Melkonian, Andrew K.; Willis, Michael J.; Pritchard, Matthew E. (Frontiers in Earth Science, 2016)
We calculate thinning rates ($\frac{dh}{dt}$) at the 5,800 km2 Stikine Icefield of southeast Alaska from stacked digital elevation models (DEMs) acquired between 2000 and 2013/2014, and glacier velocities between 1985 and 2014 from feature tracking on optical image pairs. We find a mass change rate of -3.3 $±$ 1.1 Gt yr-1 between 2000 and 2014, equivalent to an area-averaged elevation change rate of -0.57 $±$ 0.18 m w.e. yr-1. In 2014, land-terminating glaciers are 50% of the Stikine Icefield's glaciated area and contribute -0.9 $±$ 0.4 Gt yr-1 of mass change (27% of the total), while marine-terminating glaciers are only 30% of the total glaciated area, but contribute -1.5 $±$ 0.3 Gt yr-1 (or 45% of total mass change, with the remaining mass loss from lacustrine-terminating glaciers). We estimate the frontal ablation flux between 2000 and 2014 at the four largest marine-terminating glaciers on the Stikine Icefield (covering 90 to 95% of the marine-terminating glaciated area) using our glacier velocities and maps of fjord bathymetry to estimate terminus cross sections and glacier thicknesses. The combined 2014 frontal ablation flux of these four glaciers is 1.18 $±$ 0.14 Gt yr-1, which may account for the difference in average mass loss between marine- and land-terminating glaciers on the Stikine Icefield. The Stikine and adjacent Juneau Icefields have very different mass loss contributions from marine-terminating glaciers (45% vs. effectively 0%), but both have area-averaged elevation change rates that are less negative than Alaska-wide estimates, which is surprising for these southernmost icefields in Alaska.